Pengaruh Pemberian Teknik Relaksasi terhadap Tingkat Nyeri Post Partum di RSU PKU Muhammadiyah Bantul 2008 - Wijayanti, Ayun (STIKES 'Aisyiyah Yogyakarta, 2008)
Every woman would have experience of feeling pain begining from the delivery until the post partum period. Pain of post partum usualy called as afterpains, that is cramp on lower stomach which is caused uterus muscle’s contraction that happens at the first hour after delivery procces. Relaxation technique is a very effective non-pharmacology method that use to reduce pain during pos partum. The purpose of this research is to get to know the affect of giving relaxation technique toward level of pain on post partum. The observation was taken in the Obsgyn Room of “PKU Muhammadiyah” General Hospital Bantul, started in November 2007 until May 2008. The type of observation used is experimental deceit or quasi experiment which is using Non Equivalent Control Group’s design. Sample of this observation were 30 persons, where 15 respondent in group-I (experiment) and 15 respondent in group-II (control) that was taken by using sampling technique : purpose sampling. The observation’s instrument using Intensity pain of VDS scale’s form. Significant score on Mc Nemar’s statistic examination result on both groups were 0,01>0,05, this is conclude that relaxation inner breathing technique has influenced on reducing pain during post partum. Conclusion, that relaxation technique has effective influence in reducing pain in post partum. Nurse in giving nursing care to the patients should increase their participation patients through non-pharmacology manajemen, that is one of it by giving relaxation technique to reduce pain on post partum.